Embedding Child Rights Principles and Practises in Mega Sport Event Planning - Aina, Oluwaseyi; McGillivray, David; Carnicelli, Sandro; McPherson, Gayle (Frontiers in Sports and Active Living, 2021)
Recently, there has been growing concern about the lack of intentionality of mega sport event (MSE) organisers in ensuring that child rights are adequately respected, protected and promoted before, during, and after the events take place. In the context of the summer Olympic Games, reported child rights infringements have been on the rise, both in relation to abuse in sport itself and the negative consequences associated with planning and delivering the Games. In response to reports of child rights infringements, a coalition of actors, including non-governmental and civil society organisations have sought to pressure event owners and organisers to strengthen protections in the planning and delivery of their events. To date, however, child rights commitments have not been fully embedded in policies and principles guiding the planning and delivery of the Olympic Games. In this article, we explore the field of child rights in the context of the Olympic Games, focusing on a case study of the Tokyo 2020 edition. Drawing on documentary analysis and semi-structured interviews with Tokyo 2020 stakeholders and affiliates, detailed appraisal of the planning process was undertaken. Findings show that while the Japanese authorities have signed up to international child rights conventions and embedded some child participation strategies in Games-related activity, there was little evidence that Tokyo 2020 organisers had developed or implemented robust policies, principles or practises to respect, protect and promote child rights in Games planning. This absence, we argue, is because there was no requirement to embed child rights commitments during the bidding or planning phases, as the IOC had yet to enshrine human rights in its host city contract when the Games were first awarded to Tokyo. In conclusion, we argue that it is imperative the IOC embeds child rights principles and protocols in the bidding and planning processes to ensure that the risks to children are foregrounded and acted upon by host cities and their partners, elevating human rights to a position equal to other Games requirements. This study is of international significance as the evidence will aid future host city bidders to ensure children's rights are embedded in MSE policies for each nation.